Unmasking Narcissus: A competitive test of existing hypotheses on (agentic, antagonistic, neurotic, and communal) narcissism and (explicit and implicit) self-esteem across 18 samples. Issue 4 (18th May 2020) - Mota, Simon; Humberg, Sarah; Krause, Sascha; Fatfouta, Ramzi; Geukes, Katharina; Schröder-Abé, Michela; Back, Mitja D.
ABSTRACT: Research on narcissists' explicit self-esteem (ESE) and implicit self-esteem (ISE) is characterized by a wide array of competing hypotheses and inconsistent empirical findings. Using data from 18 samples (total N = 5, 547), we moved beyond classical null-hypothesis testing and employed an information-theoretic approach combined with Response Surface Analysis to provide a first competitive test of all plausible ESE-ISE combinations for different aspects of narcissism and across a wide set of ISE measures. Agentic and communal narcissism were positively, neurotic and antagonistic narcissism were negatively related to ESE. Contradicting the mask model and other more complex models, no consistent evidence was found for relations between narcissism and ISE, and ESE-ISE discrepancies, respectively. Implications for understanding narcissistic self-regulatory dynamics are discussed.